18F-FDG dynamic PET/CT in patients with multiple myeloma: Patterns of tracer uptake and correlation with bone marrow plasma cell infiltration rate - Sachpekidis, Christos; Mai, Elias K.; Goldschmidt, Hartmut; Hillengaß, Jens; Hose, Dirk; Haberkorn, Uwe (Clinical nuclear medicine, 2015)
Purpose: The value of 18F-FDG PET in the diagnostic approach of multiple myeloma (MM) remains incompletely elicited. Little is known about the kinetics of 18F-FDG in the bone marrow and extramedullary sites in MM. This study aimed to evaluate quantitative data on kinetics and distribution pattern...